STUDY ON THE LOW-VELOCITY IMPACT AND RESIDUAL COMPRESSIVE STRENGTH OF HYBRID COMPOSITE SANDWICH STRUCTURES (MT) - ZHANG ChaoFeng; HAN ChaoChao; ZHU JiaJia; DU WeiZhong (Jixie qiangdu)
The impact characteristics and residual compressive strength of the honeycomb sandwich structure under different impact energies and different boundary conditions were studied by testing and finite element analysis. The Vumat subroutine was used to establish a three-dimensional progressive failure criterion. The validity of the simulation model was verified by experiments. The results show that the simply supported specimens are more prone to damage and the peak force is lower, but the energy absorption effect is slightly better. At the same time, the residual compressive strength of the simply supported sample after impact is relatively low. When the impact energy is low, the boundary conditions have an important influence on the residual compressive strength. The influence of boundary conditions on the residual compressive strength can be ignored when the impact energy is large.